Contrast ‑ in cardiac magnetic resonance imaging. Issue 3 (23rd February 2018) - Patel, Nirav; Kolakalapudi, Pavani; Arora, Garima
Abstract : The utility and role of cardiac magnetic resonance (CMR) as a non‐invasive diagnostic imaging modality has been well recognized in the field of cardiovascular disease. Use of late gadolinium enhancement (LGE) has further enhanced CMR's ability to determine structural, functional, and prognostic information in various cardiovascular diseases. The delivery and distribution of gadolinium as an extracellular agent allows the detection of edema, fibrosis, and infiltration in the myocardium. The pattern of LGE in cardiomyopathies enables us to distinguish among various disease processes non‐invasively. Additionally, in patients with hypertrophic cardiomyopathy and sudden cardiac death, it helps in decision making in regards to use of implantable cardioverter defibrillator. In the evaluation of cardiac masses, LGE‐CMR can often times differentiate between neoplastic and non‐neoplastic conditions. In this review, we will discuss the various aspects of gadolinium‐based contrast agents, and its application in CMR.